UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE SURVEY, QUESTION, READ, RECITE, DAN REVIEW SISWA KELAS VIIB SMP TAMAN DEWASA IBU PAWIYATAN YOGYAKARTA - Andi Lestari Putro; A. A Sujadi (Universitas Sarjanawiyata Tamansiswa, 2014)
The research purposes to increases motivation and mathematics achievement with Survey, Question, Read, Recite and Review (SQ3R) learning methods in class VIIB SMP Taman Dewasa Ibu Pawiyatan Yogyakarta. Type Classroom Action Research. The research subjects were students of class VIIB SMP Taman Dewasa Ibu Pawiyatan Yogyakarta Jetis and object of this research were motivation and mathematics achievement. Techniques of data collection is using observation, questionnaire, tests, and documentation. The results showed that motivation and mathematics achievement increase. The results can be seen from motivation observation pre-term by 20.83% with low category, increased to 40.83% with the moderate category in first term. Then increased again to 66.31% in second term with the high category. The results can be seen from motivation questionnaire pre-term by 56.82% with moderate category, increased to 62.4% with the high category in first term. Then increased again to 72% in second term with the high category. The results of mathematics achievement obtained from test, with percentage completeness obtained pre-term 22.2% with an average of 59.3. In first term increased to 57.14% with an average of 66.5 and in second term increased to 78.57% with average value of 71.57.